The Implementation of In-Service Teacher Professional Education for Improving the Quality of Education in Indonesia: An Analysis of Digital Public Opinion - Sari, Iis Indah; Munawar, Fuad; Supiana, Supiana (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2024)
The purpose of this study is to analyze the extent of public perception of the implementation of the PPG program in the context of Indonesian education. This study uses a qualitative method using a deductive-inductive approach, data collection with web scraping techniques. The criteria for selecting data from comments are by selecting relevant and representative comments that include various views on the implementation of the Teacher Professional Program. The analysis technique used is to use text-based analysis to assess whether a comment is positive, negative or neutral supported by various references such as books, journal articles, and relevant references. The data in this study was taken from a post on Instagram entitled